THE IMPACT OF NON-PERFORMING LOANS ON BANKING PROFITABILITY INDICATORS: AN ANALYTICAL STUDY OF A SAMPLE OF PRIVATE COMMERCIAL BANKS LISTED ON THE IRAQI STOCK EXCHANGE - Muhanad N. Nawaf; Jamal H. Mohammed (Scholars Digest Publishing, 2024)
The research aims at a fundamental objective: to identify the impact of non-performing loans on the profitability of private commercial banks. The research problem encompasses a primary question: Is there a statistically significant impact of the non-performing loans indicator on banking profitability as represented by the return on assets (ROA), return on deposits (ROD), and return on equity (ROE)? The research is based on a set of hypotheses, the most important of which is that there is a statistically significant impact of asset quality on banking profitability. The research population consists of private commercial banks, with three banks selected based on the available data in their financial reports. The hypotheses were tested using the descriptive analytical method through (Excel 13), aiming to identify the relationship between the research variables. The researchers reached several conclusions, the most important of which is that the results showed an inverse relationship between the non-performing loans indicator and profitability indicators, as an increase in the non-performing loans indicator leads to a decrease in profitability. The researchers recommended the necessity of working seriously and efficiently to resolve non-performing loans that can be recovered from debtors, in line with the standards of loan granting.
Keywords: Non-performing loans, banking profitability.